Molecular pathophysiology and pharmacology of the voltage-sensing module of neuronal ion channels - Miceli, Francesco; Soldovieri, Maria Virginia; Ambrosino, Paolo; De Maria, Michela; Manocchio, Laura; Medoro, Alessandro; Taglialatela, Maurizio (Frontiers in Cellular Neuroscience, 2015)
Voltage-gated ion channels (VGIC) are membrane proteins that switch from a closed to open state in response to changes in membrane potential, thus enabling ion fluxes across the cell membranes. The mechanism that regulate the structural rearrangements occurring in VGIC in response to changes in membrane potential still remains one of the most challenging topic of modern biophysics. Na+, Ca2+ and K+ voltage-gated channels are structurally formed by the assembly of four similar domains, each comprising six transmembrane segments. Each domain can be divided in two main regions: the Pore Module (PM) and the Voltage-Sensing Module (VSM). The PM (helices S5 and S6 and intervening linker) is responsible for gate opening and ion selectivity; by contrast, the VSM, comprising the first four transmembrane helices (S1-S4), undergoes the first conformational changes in response to membrane voltage. In particular, the S4 segment of each domain, which contains several positively charged residues interspersed with hydrophobic amino acids, is located within the membrane electric field and plays an essential role in voltage sensing. In neurons, specific gating properties of each channel subtype underlie a variety of biological events, ranging from the generation and propagation of electrical impulses, to the secretion of neurotransmitters, to the regulation of gene expression. Given the important functional role played by the VSM in neuronal VGICs, it is not surprising that various VSM mutations affecting the gating process of these channels are responsible for human diseases, and that compounds acting on the VSM have emerged as important investigational tools with great therapeutic potential. In the present review we will briefly describe the most recent discoveries concerning how the VSM exerts its function, how genetically inherited diseases caused by mutations occurring in the VSM affects gating in VGICs, and how several classes of drugs and toxins selectively target the VSM.